Impact Of Digital Leadership on Small Medium Enterprises Resilience: The Mediating Role of Employee Creativity - Rahmat Eka Putra; Sepri Neswardi; Primadona Primadona; Jumyetti Jumyetti; Ika Yuanita (Management Institute Faculty of Economics Universitas Andalas, 2023)
Survival of Small Medium Enterprises (SMEs) is important in uncertainty and rapid advancement of digitalization nowadays, which leads to significant changes in the business environment. SMEs must be able to be resilient and face turbulence to survive and maintain business continuity. To support this resilience, digital leaders are required to help enterprises transform and lead them to a more promising future. Thus, SMEs have a digital mindset so that they can recognize and exploit opportunities, as well as overcome the challenges of surviving in an increasingly dynamic environment. Based on Social Exchange Theory and Resource Base Theory, this study examines the relationship between digital leadership and SMEs resilience through the mediation of employee creativity. Based on a sample of 179 SMEs from various sectors in Indonesia. The data were analyzed using AMOS-SEM by assessing construct validity and reliability, as well as measurement and structural models. The analysis confirms the effect of digital leadership on SMEs' resilience. The findings also provide support for the mediating role of employee creativity. The ﬁndings reveal the effect mechanism of digital leaders on SMEs resilience and enrich the literature on antecedents of SMEs resilience. Practical implications and future research are also discussed.